Reconsidering the nature and mode of action of metabolite retrograde signals from the chloroplast - Estavillo, Gonzalo M.; Chan, Kai X.; Phua, Su Yin; Pogson, Barry J. (Frontiers in Plant Science, 2013)
Plant organelles produce retrograde signals to alter nuclear gene expression in order to coordinate their biogenesis, maintain homeostasis, or optimize their performance under adverse conditions. Many signals of different chemical nature have been described in the past decades, including chlorophyll intermediates, reactive oxygen species (ROS), and adenosine derivatives. While the effects of retrograde signaling on gene expression are well understood, the initiation and transport of the signals and their mode of action have either not been resolved, or are a matter of speculation. Moreover, retrograde signaling should be considered as part of a broader cellular network, instead of as separate pathways, required to adjust to changing physiologically relevant conditions. Here we summarize current plastid retrograde signaling models in plants, with a focus on new signaling pathways, SAL1-PAP, methylerythritol cyclodiphosphate (MEcPP), and β-cyclocitral (β-CC), and outline missing links or future areas of research that we believe need to be addressed to have a better understanding of plant intracellular signaling networks.